Secure Transmission in Multi-Pair AF Relaying Massive MIMO Networks Against Active Pilot Spoofing Attacks - Xianyu Zhang; Daoxing Guo; Kang An; Xiaohu Liang; Wenfeng Ma (IEEE Access, 2019)
This paper investigates the secure transmission in multi-pair massive multiple-input multiple-output amplify-and-forward (AF) relaying networks under active pilot spoofing attacks. The AF relaying beamforming and the artificial noise generation are designed based on the imperfect estimated channel state information. Exploiting a random matrix theory, we first derive the tractable analytical expressions for the end-to-end signal-to-interference-plus-noise ratios (SINRs) at both the intended user and the eavesdropper. Then, we provide the asymptotic results for derived SINRs with respect to the infinite number of relay antennas, unbounded transmit power, and relay power, which show that the SINRs at intended user and eavesdropper are both limited by specific bounds and the effects of relay noise or received additive noise will be eliminated in these extreme power cases. Moreover, power scaling laws are studied to reveal that only the scaled relay power is effective, while source power has no scaling properties for secure transmission in the considered system. To mitigate the severe information leakage, by superimposing a random detection pilot sequence on the training sequence, a simple method based on the minimum description length criterion is provided to detect the presence of the pilot spoofing attacks. The numerical results are provided to confirm the accuracy of our theoretical derivations and illustrate the effectiveness of the proposed scheme.